A disciplina do desenho: (des)construções no espaço escolar - Andreia Tamára Nogueira Lisboa (2022)
This report starts from the contextualization of the pedagogical internship experience and the reflection on the place of intern, which wandered through the place of student, recognizing the students as voiceless subjects in the school context and the teacher as a professional who sees himself subordinated to a set of directives, in a somewhat mechanized school system. In a school where equality and inclusion are promoted, it becomes relevant to analyze and question official discourses in relation to practices that actually take place on the ground, which can prove to be marginalizing. In the same school, it was identified the problem that occupies much of the writing, related to the perpetuation of a disciplined drawing, closed to contemporary artistic practices, to processes of transformation and reflection, endowed with evaluative methods focused on the constant pointing out of the right and the wrong. What contributed to a certain distance and lack of identification of the student with the Drawing A subject. In this report, it is about dismantling and deconstructing certain narratives of drawing at school, suggesting, through the critical reflection and the developed didactic activity, drawing as a broad field, composed of a range of possibilities and unpredictability. Open to contemporaneity, in which synergies are also created with references from the past, to the detriment of a drawing solely and exclusively linked to reproduction of the image and technical skill, devaluing other discourses considered disruptive. The internship experience also led to the transformation of idealizations prior to the internship, namely about being a teacher, reflecting their impact on the initial view about the drawing practices observed in the school. Therefore, the report, in addition to a critical analysis of the identified problem, also includes a critical reflection of the narratives and codes that were instilled and naturalized along the way as a student.